2011
DOI: 10.1245/s10434-010-1526-x
|View full text |Cite|
|
Sign up to set email alerts
|

Surgical Treatment of Renal Cell Cancer Liver Metastases: A Population-Based Study

Abstract: BackgroundTo evaluate outcomes of surgical treatment in patients with hepatic metastases from renal-cell carcinoma in the Netherlands, and to identify prognostic factors for survival after resection. Renal-cell carcinoma has an incidence of 2,000 new patients in the Netherlands each year (12.5/100,000 inhabitants). According to literature, half of these patients ultimately develop distant metastases with 20% involvement of the liver. Resection of renal-cell carcinoma liver metastases (RCCLM) is performed in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 22 publications
4
55
0
2
Order By: Relevance
“…Moreover, these results compare favorably to those of hepatic resection for hepatic metastases 13. Our series of patients adds to this limited data set and will hopefully lead to hypothesis generation in order to formulate further trials.…”
Section: Discussionmentioning
confidence: 58%
“…Moreover, these results compare favorably to those of hepatic resection for hepatic metastases 13. Our series of patients adds to this limited data set and will hopefully lead to hypothesis generation in order to formulate further trials.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, liver surgery is accepted as a treatment option in patients with neuroendocrine liver metastases (NELM), with 5-year survival ranging from 60 to 80% [4,5,6]. Selected patients with non-CRLM, non-NELM may also be potential candidates for surgical treatment, since several studies demonstrated an association with improved survival after liver resection [7,8,9,10,11,12]. …”
Section: Introductionmentioning
confidence: 99%
“…A similar French study reported an increase in liver resection from 2 to 20% in the period between 1976 and 2000 [22]. In both studies, only patients with liver metastases from colorectal origin were evaluated, and only few nationwide studies are available on liver resections performed for non-CRLM [8,10,12]. …”
Section: Introductionmentioning
confidence: 99%
“…There has been an increase in the incidence of RCC in recent years. More than one-third of patients with RCC have evidence of metastases at the time of diagnosis, and approximately 33% develop systemic recurrence after primary tumor resection [4,5]. The lung is the most common site of distant recurrence.…”
Section: Introductionmentioning
confidence: 99%